2020
DOI: 10.1038/s41598-020-64405-6
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of lung auscultation in adult patients with acute pulmonary pathologies: a meta-analysis

Abstract: The stethoscope is used as first line diagnostic tool in assessment of patients with pulmonary symptoms. However, there is much debate about the diagnostic accuracy of this instrument. This metaanalysis aims to evaluate the diagnostic accuracy of lung auscultation for the most common respiratory pathologies. Studies concerning adult patients with respiratory symptoms are included. Main outcomes are pooled estimates of sensitivity and specificity with 95% confidence intervals, likelihood ratios (LRs), area unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 58 publications
(66 reference statements)
1
36
0
2
Order By: Relevance
“…Of the included studies, 75% used lung ultrasonography in concert with other modalities, making it difficult to ascertain which effects can be exclusively attributed to lung ultrasonography. This might be considered inconsequential as lung ultrasonography should not be viewed as a replacement but an extension of physical examination and conventional management (Covic et al 2018;Picano et al 2018;Mojoli et al, 2019;Arts et al 2020). This is in line with a previous study that found an integrated ultrasonographic approach, in the form of thoracic ultrasonography, outperforms its individual components (Bataille et al 2014).…”
Section: Very Low ◌◌◌supporting
confidence: 74%
“…Of the included studies, 75% used lung ultrasonography in concert with other modalities, making it difficult to ascertain which effects can be exclusively attributed to lung ultrasonography. This might be considered inconsequential as lung ultrasonography should not be viewed as a replacement but an extension of physical examination and conventional management (Covic et al 2018;Picano et al 2018;Mojoli et al, 2019;Arts et al 2020). This is in line with a previous study that found an integrated ultrasonographic approach, in the form of thoracic ultrasonography, outperforms its individual components (Bataille et al 2014).…”
Section: Very Low ◌◌◌supporting
confidence: 74%
“…In the absence of radiology, general practitioners are reliant upon empirical diagnosis of CAP using auscultation or clinical signs resulting in a significant proportion (71%) of radiologically-confirmed CAP cases being missed in primary care (27). Clinical signs and symptoms have previously been shown to perform poorly in the diagnosis of CAP (6, 8). Our algorithm provides high diagnostic accuracy in the absence of radiology and without the need to examine the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, clinical symptoms and signs in isolation have generally performed poorly as diagnostic criteria (5). Auscultation findings alone have poor sensitivity and demonstrate poor agreement between clinicians (6-8). Vital sign measurements are recommended to rule out CAP: a systemic review in 2019 showed validity using a combination of breathing rate, heart rate and fever (-ve LR, 0.24 (0.17 to 0.34) (9).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of radiology, general practitioners are reliant upon empirical diagnosis of CAP using auscultation or clinical signs resulting in a significant proportion (71%) of radiologicallyconfirmed CAP cases being missed in primary care (28). Clinical signs and symptoms have previously been shown to perform poorly in the diagnosis of CAP (6,8). Our algorithm provides high diagnostic accuracy in the absence of radiology and without the need to examine the patient.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“… 7 Auscultation findings alone have poor sensitivity and demonstrate poor agreement between clinicians. 8 10 Vital sign measurements are recommended to rule out CAP: a systemic review in 2019 showed validity using a combination of breathing rate, heart rate, and fever (negative likelihood ratio 0.24, 95% confidence interval [CI] = 0.17 to 0.34). 11 …”
Section: Introductionmentioning
confidence: 99%